A Comparative Regional Perspective on Alternative Action Organization Responses to the Economic Crisis Across Europe. (May 2018) - Cristancho, Camilo; Loukakis, Angelos
Solidarity alternatives have emerged as the response of organized social activists to periods of economic hardship all over the world, in different times. This article explores to what extent such activities have emerged across European regions following the financial crisis of 2008. Research has addressed the relationship between the economic context and the emergence of alternative action groups, tracing their spatial variation, but few works offer systematic comparative data at the regional level. This article offers a spatial overview of temporal changes among 2, 600 Alternative Action Organizations (AAOs) at the regional level in nine European countries, before and after 2008. It also provides evidence of how the number of AAOs and their focus on the most needy change as a function of the intensity of the crisis and its effect on the poor and unemployed. We find no differences between countries either in terms of the number of emerging AAOs nor in their capacity to refocus their attention on the most needy, due to the intensity or type of crisis. We thus confirm existing research that explains alternative action as a response to crisis within the context of resourced and experienced social action organizations rather than as a direct reaction to economic hardship. Our results provide comprehensive evidence across multiple contexts showing that social resilience through alternative action is not produced directly by contextual distress but seems to be mediated by existing resources. This is relevant to understanding the mechanisms behind the widely acknowledged claim that alternative economies arise in contexts of economic crisis.